Health expenditure and health status in Northern and Southern Nigeria: a comparative analysis using National Health Account Framework (2013)
Introduction: The financing of healthcare by government in Nigeria is complemented by contributions from the household, donor agencies, and the private sector. This paper examines the disparity in healthcare financing flows between the northern and southern regions of Nigeria and the implication for health outcomes. Methods: The paper uses data from the latest round of Sub-National Health Accounts for 17 states in Nigeria, from 2003 to 2005. The methodology was structured to give a complete accounting of all spending on health, regardless of the origin, destination, or object of the expenditure. Results: The paper found that healthcare financing in the north is relatively lower, accompanied by significant poor health status, with heavy dependence on the households in both regions. The share of households in the north was proportionally disproportionate, because of the high poverty incidence vis-a-vis public providers. This raises equity concerns as those least able to pay were made to bear more burden. Conclusion: The stewardship role of the government has to increase in terms of funding health care, in the light of low income of majority of the people, especially in the north, if the health status of the populace is to improve. Without government being directly involved in the provision of healthcare services, attempt should be made to subsidise the private sector health services to the citizenry. The pooling mechanism approach is identified to be an appealing alternative to finance healthcare.